2016
DOI: 10.17759/cpp.2016240511
|View full text |Cite
|
Sign up to set email alerts
|

Co-experiencing as a Key Category of Co-experiencing Psychotherapy

Abstract: * Василюк Федор Ефимович, доктор психологических наук, главный научный со-трудник лаборатории консультативной психологии и психотерапии «ПИ РАО»; зав. кафедрой индивидуальной и групповой психотерапии факультета консуль-тативной и клинической психологии МГППУ; профессор кафедры психологии личности МГУ имени М.В. Ломоносова, Москва, Россия, e-mail: fevasil@list.ru Есть три типа этических реакций на беду другого человека -сочувствие, совет, практическая помощь (М.М. Бахтин). Основа всех этих форм житейской пси-хо… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…It is usually indicated that, like any other requirement, the ethical principle of counselling, confidentiality is not an absolute requirement. In situations where there is a real threat to the life of the consultant or his environment, the psychologist must announce the information he knows about this [25,26,27].…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually indicated that, like any other requirement, the ethical principle of counselling, confidentiality is not an absolute requirement. In situations where there is a real threat to the life of the consultant or his environment, the psychologist must announce the information he knows about this [25,26,27].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Non-judgmentalism also provides freedom of self-examination, which acts as the essence of the counselling process: any hint of assessment, any possibility of assessment, even a positive one, limits effectiveness, immediately including those psychological defences that each of us has, imposing restrictions on the process of self-examination, on any approximation to painful experiences. It provides inclusion in the counselling and psychotherapy, as well as detachment, distancing, and withdrawal of the consulted from the process, it provides the comfort of the consultee's feelings [25,27].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…They stimulate the predominance in self-interpretation of one of the mental processes (faith, thinking, and intuition) and set three possible frameworks for interpreting the path of life -'fate-fulfillment-faith'; 'chance-incidentintuition'; 'free will-deed-thinking'. Vasilyuk (1984) was the first who identified the characteristics of lifeworlds. In his opinion, 'lifeworld' has external and internal perspectives, which he defined, respectively, as external and internal worlds.…”
Section: Developmental Psychologymentioning
confidence: 99%
“…Василюк проводит и по отношению к сопереживанию. Соответственно, сопереживание понимается не просто как эмоциональный отклик на переживание Другого, а как деятельность, направленная на содействие продуктивному ходу переживания-деятельности клиента [7]. Произвольная организация сопереживания и ее деятельностный характер означают в частности, что сопереживание протекает не по законам эмоциональных состояний и реакций, а по законам той деятельности…”
unclassified